1999
DOI: 10.1007/s004390050940
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan for loci linked to forearm bone mineral density

Abstract: Osteoporosis is a chronic disorder characterized by low bone mass and fragility fractures. It affects more than 25 million men and women in the United States alone. Although several candidate genes, such as the vitamin-D-receptor gene or the estrogen-receptor gene, have been suggested in the pathogenesis of osteoporosis, the genetic dissection of this disorder remains a daunting task. To search systematically for chromosomal regions containing genes that regulate bone mineral density (BMD), we scanned the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 35 publications
7
93
0
1
Order By: Relevance
“…Marker D2S405 in the same region on 2p23 was reported to be linked to forearm BMD by Niu et al 23 Other regions where we observed interesting lod-scores coincide with regions reported in other studies and/or known to contain candidate genes for bone-related traits. 5,12 A formal meta-analysis will help elucidate whether these findings may in fact indicate the existence of genomic regions containing susceptibility genes for osteoporosis shared across different populations.…”
Section: Discussionsupporting
confidence: 89%
“…Marker D2S405 in the same region on 2p23 was reported to be linked to forearm BMD by Niu et al 23 Other regions where we observed interesting lod-scores coincide with regions reported in other studies and/or known to contain candidate genes for bone-related traits. 5,12 A formal meta-analysis will help elucidate whether these findings may in fact indicate the existence of genomic regions containing susceptibility genes for osteoporosis shared across different populations.…”
Section: Discussionsupporting
confidence: 89%
“…However, the identity of specific genes and their relative effects on BMD\BMC variation are unknown. The few studies are inconsistent in the existence and\or identification of major genes for BMD\BMC (Gueguen et al 1995 ;Livshits et al 1996Devoto et al 1998 ;Niu et al 1999 ;Duncan et al 1999 ;Koller et al 2000 ;Cardon et al 2000 ;. In 51 human pedigrees with 941 individuals (526 measured for phenotypes) identified via probands with extreme BMD values, we performed complex segregation analyses to test for the existence of a genetic locus with a major effect on BMD\BMC variation.…”
Section: mentioning
confidence: 99%
“…However, there are still very few segregation analyses in the bone genetic field, even when compared with linkage studies. The linkage studies in the bone field (Devoto et al 1998 ;Niu et al 1999 ;Koller et al 2000) have almost all been conducted without prior segregation analyses ; therefore, the likelihood of success cannot be assessed for the study designs and samples even if statistical genetic power analyses were performed. This is because the statistical power analyses require an assumed effect of a putative major gene that can only be ascertained via segregation analyses prior to linkage analyses for complex traits.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations